The Potential Role of Herpes Simplex Virus Type 1 and Neuroinflammation in the Pathogenesis of Alzheimer's Disease - Laval, Kathlyn; Enquist, Lynn W. (Frontiers in Neurology, 2021)
Alzheimer’s disease (AD) is a neurodegenerative disease affecting approximately 50 million people worldwide. To date, there is no cure and current therapies have not been effective in delaying disease progression. Therefore, there is an urgent need for better understanding of the pathogenesis of AD and to rethink possible therapies. Herpes simplex virus type 1 (HSV1) has recently received growing attention for its potential role in sporadic AD. The virus is a ubiquitous human pathogen that infects mucosal epithelia and invades the peripheral nervous system (PNS) of its host to establish a reactivable, latent infection. Upon reactivation, HSV1 spreads back to the epithelium and initiates a new infection, causing epithelial lesions. Occasionally, the virus spreads from the PNS to the brain after reactivation. In this review, we discuss current work on the pathogenesis of AD and summarize research results that support a potential role for HSV1 in the infectious hypothesis of AD. We also highlight recent findings on the neuroinflammatory response, which has been proposed to be the main driving force of AD, starting early in the course of the disease. Relevant rodent models to study neuroinflammation in AD and novel therapeutic approaches are also discussed. Throughout this review, we focus on several aspects of HSV1 pathogenesis, including its primary role as an invader of the PNS, that should be considered in the etiology of AD. We also point out some of the contradictory data and remaining knowledge gaps that require further research to finally fully understand the cause of AD in humans.